2021
DOI: 10.1017/pds.2021.534
|View full text |Cite
|
Sign up to set email alerts
|

Structuring Human Augmentation Within Product Design

Abstract: Human augmentation is a thriving research field that aims to amplify human abilities through the development of technological improvements as an integral part of the human body. Human augmentation products may be made for anyone, ranging from healthy users wanting to enhance their human abilities to users who face temporary or permanent disabilities, physical impairments, or perilous situations that oblige them to use these products.This article attempts to introduce readers to the domain of human augmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…The full texts of 83 papers assessed for eligibility were carefully analyzed. Thirteen articles [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] were excluded due to the exclusion criteria (1), one contribution [ 29 ] due to the exclusion criteria (2), 17 scientific results [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] due to the exclusion criteria (3) and 5 [ 47 , 48 , 49 , 50 , 51 ] contributions due to the exclusion criteria (4). Finally, only 47 studies were included in the quantitative synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…The full texts of 83 papers assessed for eligibility were carefully analyzed. Thirteen articles [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] were excluded due to the exclusion criteria (1), one contribution [ 29 ] due to the exclusion criteria (2), 17 scientific results [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] due to the exclusion criteria (3) and 5 [ 47 , 48 , 49 , 50 , 51 ] contributions due to the exclusion criteria (4). Finally, only 47 studies were included in the quantitative synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…Sensory augmentation technology, a specific type of human enhancement technology (De Boeck and Vaes, 2021), however, may be more suitable to help bridge this sensory gap (van Dartel and de Rooij, 2019).…”
Section: A Sensory Gap Between Deaf and Hearing Peoplementioning
confidence: 99%
“…This could be done by providing sensory augmentations that enable deaf and hearing people to sense signals that neither person is able to sense with their biological senses (Berta, 2020). For example, the artwork in Figure 1 could hypothetically be adapted to be more aesthetically pleasing, e.g., a more balanced composition (McManus et al, 2011), when using an augmentation that extends color vision to sensing infrared and ultraviolet light (De Boeck and Vaes, 2021), than without. It is conceivable that well-chosen augmentations can enable a shared sensory experience between deaf and hearing that bypasses the potential challenges that deaf and hearing people run into during an encounter.…”
Section: Sensory Augmentation Technologymentioning
confidence: 99%
“…Moreover, the interdisciplinarity of the field implies a multitude of possibilities for enhancing an individual's sensory, physical, cognitive or social capabilities. As a previous study concluded, augmentation of users' social ability has not been thoroughly studied to date, despite its considerable future value (De Boeck & Vaes, 2021). Therefore, social augmentation is the focus of this study, which aims to enhance users' social capabilities by supporting collaboration, empathy, interaction and communication through wearable technology (Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%